2021
DOI: 10.3390/agriculture11020099
|View full text |Cite
|
Sign up to set email alerts
|

Competition Effects and Productivity in Oat–Forage Legume Relay Intercropping Systems under Organic Farming Conditions

Abstract: Cereal-legume intercropping is important in many low-input agricultural systems. Interactions between combinations of different plant species vary widely. Field experiments were conducted to determine yield formation regularities and plant competition effects of oat (Avena sativa L.)–black medick (Medicago lupulina L.), oat–white clover (Trifolium repens L.), and oat–Egyptian clover (T. alexandrinum L.) under organic farming conditions. Oats and forage legumes were grown in mono- and intercrops. Aboveground dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…(2022) also indicated an increase in micronutrient uptake, including Fe, with subsequent pea growth stages. There is a significant increase in biomass from the flowering stage to the green pod stage (Gecaitė et al., 2021). Accordingly, in our study, with the increase in Fe and Mn content in the forage (Table 2), an increase in Fe and Mn intake was noted (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…(2022) also indicated an increase in micronutrient uptake, including Fe, with subsequent pea growth stages. There is a significant increase in biomass from the flowering stage to the green pod stage (Gecaitė et al., 2021). Accordingly, in our study, with the increase in Fe and Mn content in the forage (Table 2), an increase in Fe and Mn intake was noted (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…As far as GY of legumes were concerned, sole crops of green and black grams remained unmatched while their grain yields were significantly reduced by three double rows (90 cm apart) of maize with three sets of quadratic rows (20 cm apart) of green or black gram (Table 3). Comparatively higher productivity of legumes monocultures might be due to better aeration, more ground area available for nutrition uptake and less shading effect of maize strips [45][46][47][48] which ultimately slashed the GY of inter-seeded legumes. These results are in agreement with [1,10,11], who reported that in cereal-legumes intercropping, legumes remained recessive compared to cereals in terms of acquiring growth resources which led to reduction in their yields compared to solo crops.…”
Section: Discussionmentioning
confidence: 99%
“…Relay intercropping is an agroecological practice that allows the cultivation of two or more crops that complementarily exploit resources within time and space while limiting the use of external inputs [5,6]. It is considered a valuable tool for the agroecological transition of current cropping systems and aims to optimize crop yields while ensuring ecosystem sustainability, resilience, profitability, and yield stability amidst the changing climatic conditions [2,7], particularly in low-input and organic farming systems [8]. Under low-input systems, durum wheat (Triticum durum Desf.)…”
Section: Introductionmentioning
confidence: 99%